Effect of surface modification of cellulose nanocrystal on nonisothermal crystallization of poly(β-hydroxybutyrate) composites. (10th February 2017) - Chen, Jianxiang; Wu, Defeng; Tam, Kam C.; Pan, Keren; Zheng, Zhigong
Highlights: Ring-opening polymerization ofl -lactide on CNC surface yields CNC- g -PLA. Pristine CNC acts as the nucleation agent, promoting crystallization of PHB. CNC- g -PLA acts as the antinucleation agent, retarding PHB crystallization. Lamellar structure of PHB is not evidently affected by the two nanoparticles. Nucleation dominates the overall process of crystallization of PHB composites. Abstract: Ring-opening polymerization ofl -lactide from cellulose nanocrystal (CNC) surface yielded polylactide-grafted CNC (CNC- g -PLA). The structure and chemical composition of the CNC- g -PLA were characterized by FT-IR, 1 H NMR, XPS and XRD. The crystallization behavior and lamellar structure of poly(β-hydroxybutyrate) (PHB) in the presence of pristine CNC and CNC- g -PLA were elucidated via DSC and SAXS, and Babinet's reciprocity theory was applied. Crystallization kinetics were further analyzed using Ozawa, Mo and Kissinger models. In the presence of pristine CNC, nucleation of PHB crystals led to an increase in the crystallization temperature ( T c ) of PHB; while CNC- g -PLA acted as antinucleation agent, resulting in a remarkable reduction in T c of PHB. Accordingly, the composite with pristine CNC possessed a higher crystallization rate than neat PHB, while CNC- g -PLA displayed the lowest crystallization rate. However, the lamellar structure of PHB was not affected by the presence of pristine and modified CNCs, and almost identical crystallization activation energies as the neat PHB were observed, indicating that nucleation is dominant during PHB crystallization, instead of crystal growth. This study offers a promising approach of using pristine and modified CNCs to control the crystallization of biodegradable aliphatic polyesters.